Mobile attendance tracking system (MobATS) focuses on access point and student module / Wan Muhammad Izzat Ifwat Wan Ab Rahman - Wan Ab Rahman, Wan Muhammad Izzat Ifwat (2013)
Each student must attend their class and sign in their attendance. Their attendance are in the form of paper which have several columns consists of name, number matrix , class, date and student's sign. In the traditional ways student must fill the attendance according to the date that are written by the lecturer only. With this style, student can copy their buddy's sign if their buddy not attend the class. This attendance also may or can loss or misplace. Since the attendance are given in the end of the class, it will make student wonder if they have sign or not. This because at that time student will not notice after the 2 hours of lesson's session by lecturer. The attendance sheet are easy to keep but it will burden the lecturer to hold with other books. The objectives of this module is to ease the student to sign up their attendance using mobile phone. This system are create to provide the connectivity to access point(AP).AP are use to as medium to access internet everywhere in the faculty. Besides that, to help student to ensure that the student attend that day. This system are easy to manage all of the student based on their subject on that semester. This system will make the student farmiliar with the environment where nowadays internets are the important element to be access at anywhere to get the information or resource quickly. In this project we are going to use Rapid Application Development(RAD). This is the best choice if we have a smaller project to manage. It will improve the efficiency of the project to be finish without any hesitation. Phase by phase are being explained in this RAD to get overview about the project. The result can become positive if all the procedure, method, timeline are in order to follow with. This project can give many benefit for the student and lecturers in the future. Research has been made before, comparison and the different can be outlined so that it can be finish within the time given. At the end, with the project done it can be take to be implement in the university to aid lecturer or others so we can achieved better.